THE DEVELOPMENT OF CROWDFUNDING IN INDONESIA - Veronika Santi Paramita (Komitmen: Jurnal Ilmiah Manajemen, 2023)
Crowdfunding is a platform that can be used to collect funds from the public. In Indonesia itself, crowdfunding is still growing. This research attempts to look at the development of crowdfunding in Indonesia. This research will be carried out using a descriptive qualitative approach. The data used in this research was obtained through the results of a literature study. The results of this research then found that the existence of crowdfunding in Indonesia is still less than optimal. Various factors such as lack of literacy mean that credit loans are still more commonly used. Therefore, there needs to be an effort to optimize crowdfunding in Indonesia. This can be achieved by maximizing the branding and quality of the crowdfunding platform, improving regulations and security, as well as exposing the existence of crowdfunding to the general public.